Rival enlightenments : - Hunter, Ian (Cambridge University Press, 2001)
Rival Enlightenments is a major reinterpretation of early modern German intellectual history. Ian Hunter treats the civil philosophy of Pufendorf and Thomasius and the metaphysical philosophy of Leibniz and Kant as rival intellectual cultures or paideia, thereby challenging all histories premised on Kant's supposed reconciliation and transcendence of the field. This landmark study argues that the marginalization of civil philosophy in post-Kantian philosophical history may itself illustrate the continuing struggle between the rival enlightenments. Combining careful scholarship with vivid polemic, Hunter presents penetrating insights for philosophers and historians alike.